The use of enabling tests to provide a qualitative measurement of the sport skill level of small soccer players - Esposito, G.; Ceruso, R.; Valentini, M.; D'Isanto, T. (Journal of Human Sport & Exercise, 2019)
Evaluation tests represent a fundamental step in the educational path of working with small football players. The method used is of an experimental type whose aim is to analyse the capacity of children in the execution of three fundamental technical aspects of football: Short and Long Passage, Header shot and Shot on Target from a stationary position and in movement. We want to emphasize the importance of training the technical gesture starting from the little ones. In fact, too much tacticism combined with a continuous search for physicality in every area of the field has produced in the last decade an innumerable series of technically poorly trained players. The tests were performed on a sample of 12 children of 10 years old that play championship under-10. The data shows the score from each child during the execution of the various tests from which the total result was obtained by adding the points awarded for each attempt. The average of the high scores for the various tests was 13 for short pass; 27.3 for long pass; 3.6 for the header shot t; 9.6, and 7.75 respectively for stationary and moving shot on goal. The results can be used at the beginning of the activity and when a new group is available to identify the gaps to work on and then they can be repeated in other and different periods of the season to verify how effective the work done up to that point was.